The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1997
DOI: 10.1116/1.580477
|View full text |Cite
|
Sign up to set email alerts
|

Ion assisted deposition of thin films by substrate tuned radio frequency magnetron sputtering

Abstract: The substrate tuning technique was applied to a radio frequency magnetron sputtering system to obtain a variable substrate bias without an additional source. The dependence of the substrate bias on the value of the external impedance was studied for different values of chamber pressure, gas composition and rf input power. A qualitative explanation of the results is given, based on a simple model, and the role of the stray capacitance is clearly disclosed. Langmuir probe measurements show that this system allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The RF input power was 350 W, and the reflected power was reduced to zero by an impedance adapter. On the other hand the substrate bias voltage was kept to a positive value of +10 V using the tuned RF magnetron sputtering technique [14]. A reactive mixture of Ar and N 2 was introduced The resulting 10 B 4 C layer showed excellent homogeneity over the whole wafer.…”
Section: Boron Carbide Depositionmentioning
confidence: 99%
“…The RF input power was 350 W, and the reflected power was reduced to zero by an impedance adapter. On the other hand the substrate bias voltage was kept to a positive value of +10 V using the tuned RF magnetron sputtering technique [14]. A reactive mixture of Ar and N 2 was introduced The resulting 10 B 4 C layer showed excellent homogeneity over the whole wafer.…”
Section: Boron Carbide Depositionmentioning
confidence: 99%
“…Films were grown without intentional heating on silicon (Si) (100) wafers for different values of the discharge gas composition, the total pressure, and the substrate self-bias voltage. The temperature of the films during the process remained below 200 • C. For this work, samples of series A were deposited with the substrate holder electrically isolated, and samples of series B were grown after connecting the holder to the ground through an external tuning network, which is a convenient way to control the substrate self-bias voltage [6]. A direct current (DC) bias probe formed by a RF rejection filter and a voltage divider was used to measure the DC bias substrate voltage with respect to the anode (ground).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is important to understand the electrode impedance effect in designing a plasma process apparatus. The effect of an external circuit on plasma properties has been studied for over 20 years [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The electrode impedance effects discussed in these studies can be categorized into linear and nonlinear effects.…”
Section: Introductionmentioning
confidence: 99%
“…The linear electrode impedance effect is caused by the impedance at the externally applied frequency. Several authors have reported the control of self-bias by using an external circuit in physical vapor deposition (PVD) chambers [1][2][3]. In their studies, 13.56 MHz RF was applied to an ICP antenna to generate plasma, and the impedance of the wafer was tuned using an external circuit.…”
Section: Introductionmentioning
confidence: 99%